COMPONENTS OF BEHAVIOURAL FINANCE IN INVESTMENT DECISION - Dr. K. KANIMOZHI , Dr. T. S. ARCHANA (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
An investment on the basis of portfolio has become complex as people invested large sum of money even when there is a little change of investment being profitable. Most of the investors have rational expectations and maximize their utility. In the posture of investor, it is vitally important to understand why certain financial decisions are made or how people are likely to react in common conditions of uncertainty. This form of analysis is useful in an attempt to understand how a person can temper the irrational components of investment decisions while still satisfying the individual preferences and requirements.